The impact of phasing out subsidy for financial performance of photovoltaic enterprises: evidence from “531 new policy” on China’s photovoltaic industry - Yang, Lianfen; Hua, Hongyan; Zhang, Jie (Frontiers in Energy Research, 2024)
In the past two decades, China’s government subsidy policy has promoted the rapid development of the photovoltaic industry. Concerns have been raised about how the financial performance of China’s photovoltaic firms changes with the gradual cancellation of subsidies. Taking the “531 New Policy” of China’s photovoltaic industry as an exogenous shock, based on the sample of listed companies in Shanghai and Shenzhen A-share photovoltaic industry from 2015 to 2023, this paper uses the diference-in-diferences model to study the impact of the phasing out subsidy on the financial performance of photovoltaic enterprises from the micro level. The study found that the implementation of the “531 New Policy” significantly reduced the financial performance of photovoltaic enterprises in general. Considering the difference of industrial chain links, the negative impact of decreasing subsidies on the financial performance of downstream photovoltaic enterprises is more significant, among which R&D investment plays a partially intermediary role. In addition, the phasing out subsidy has a more significant negative impact on the financial performance of senior and eastern enterprises than young and midwest enterprises. The conclusions of this study have important practical implications for photovoltaic enterprises’ decision-making under the changing external policy environment.